Sunday

April 20, 2014

April 20, 2014

Posted by **think I got it** on Saturday, May 26, 2007 at 12:23am.

F(x)= 2(-3a) -5

F(-3a) = 2(3a)-5

= 1

did I do this right?

You went from:

f(-3a)

to

f(3a)

Also, what happened to the "a?"

Matt

**Related Questions**

Math(Please Check My Work.) - 3a^3b^2(-a^3b-a^2b^2)=-3a^9b^3-3a^6b^4 *is this ...

Pre-Calc-please check - Please check this for me expand (3z-2b)^5 using Binomial...

algebra - 3ax^2 - 27a You can factor that into 3a (x^2 - 9), which also equals ...

math - simplify 12b^-6/3a^0 you should read my notes on "rob"'s questions if you...

math - x+a=b/3x x= ? i understand that u bring the x to one side but the answer ...

Math- factoring - Show all work and factor completely. 6a^2+5a-4 (6a^2+8a)-(3a-4...

algebra - Given g(x) = –2x – 1, find g(3a). G(3a)=-2(3a)-1 = -6a-1 = -5 is this ...

algebra - Given f(x) = 2x - 5, find f(-3a). okay were does the a come in here? ...

Math - Factor each expression 1-9a^2/a+1 times 4x^2-y^2/x+y Here is what I got...

maths algebra - 3a-2(2a+4) 3a-2(2a + 4) you multiply the parenthesis by -2, ...